2021
DOI: 10.1259/dmfr.20200313
|View full text |Cite
|
Sign up to set email alerts
|

Positioning accuracy assessment of minimally invasive percutaneous injection techniques for the treatment of temporomandibular disorders

Abstract: Objective: The aim of the present study was to evaluate the accuracy of an extraoral CBCT-planned 3D-printed surgical guide aimed to percutaneous injection of substances into the temporomandibular joint (TMJ) and the lateral pterygoid muscle (LPM). Methods: Nine human cadaver heads were used. Pre-planning CBCT and facial scans were obtained and three percutaneous injection sites were planned: one for the lower compartment of the TMJ and two for the LPM. A digital surgical guide was then designed with small tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In addition, one article reported prolotherapy directed at the IJS with injection of hypertonic dextrose solution with local anaesthetic 30 . Non‐patient‐based studies report HA injection to the IJS, 25 dye solution injection for post‐dissection analysis 32,34 and needle insertion without solution infiltration 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one article reported prolotherapy directed at the IJS with injection of hypertonic dextrose solution with local anaesthetic 30 . Non‐patient‐based studies report HA injection to the IJS, 25 dye solution injection for post‐dissection analysis 32,34 and needle insertion without solution infiltration 33 …”
Section: Resultsmentioning
confidence: 99%
“…Custódio et al used a CBCT-planned 3D-printed surgical guide to insert the needle in the IJS showing very small variations in the angle, length and dislocation of the needle between the planned and the actual insertion. 33 Although the conclusion indicates that the guide seems to be a reliable tool for accurate percutaneous injection of drugs into the IJS, it is noteworthy that CBCT cannot identify the disk nor superior or inferior spaces 47 thus the results achieved seem at least questionable given that there is no real evidence that the needle was positioned into de IJS, nevertheless the method seem promising if it can be combined with MRI. Cadaveric studies show mixed results in terms of efficacy to reach the IJS, reporting success rates that varied between 30% 32 and 92%.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method was also tested in a pilot study and the potential for this application was demonstrated. The results of precision and trueness, including needle deviations and depth measurements, for this study, has been covered in another publication [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In minimally invasive or atraumatic surgery or dental procedures, there are several clinical studies with increasing expectations to establish treatment guidelines. This selection of data was due to the significant increase in quantitative synthesis methods in the dental literature from the beginning of the 21st century [1,2]. Most of the selected studies were carried out in the USA, Netherlands, and UK.…”
Section: Introductionmentioning
confidence: 99%